PENGARUH KEWAJARAN HARGA DAN KEWAJARAN PROMOSI TERHADAP LOYALITAS PELANGGAN (Studi Pada Toserba Borma Dakota) - Tiyan Sutiyani (FEB Universitas Sultan Ageng Tirtayasa, 2018)
Supermarket has growed up especially in area Bandung, consumers are exsposed to many choices. Many choice make the question of whether customers feel they receive price fairness if they prefer to shop in supermarket? How they feel with promotion fairness in supermarket? Result of research got that price and promotion in Toserba Borma Dakota describe fairness and customer loyalty Toserba Borma Dakota described fairness and customer loyalty Toserba Borma Dakota described loyal. The price fairness has a positive effect on customer loyalty with a path coefficient of 30.5%. Similarly, the promotion fairness has positive effect on customer loyalty with a path coefficient of 35.0%.